Lavandula x intermedia and Lavandula angustifolia essential oils: phytochemical composition and antimicrobial activity against foodborne pathogens. Issue 22 (17th November 2019) - Tardugno, Roberta; Serio, Annalisa; Pellati, Federica; D'Amato, Serena; Chaves López, Clemencia; Bellardi, Maria Grazia; Di Vito, Maura; Savini, Vincenzo; Paparella, Antonello; Benvenuti, Stefania
Abstract: Four cultivars (cv) of Lavandula x intermedia ('Abrialis', 'Alba', 'Rinaldi Ceroni' (R.C.) and 'Sumiens') were cultivated in Italy and their essential oils (EOs) were distilled from Alfalfa Mosaic Virus-free plants. These EOs and one from L. angustifolia Miller were chemically characterised by GC-MS and GC-FID. Antimicrobial activity was evaluated against Listeria monocytogenes (24 strains) and Salmonella enterica (10 food strains). Minimal inhibitory concentrations (MIC) ≥ 10.0 μL/mL inhibited Salmonella (cv 'R.C.' was the most active); MIC of 0.3 μL/mL for cv 'Abrialis' and 'R.C.' inhibited L. monocytogenes, revealing noticeable activity, especially on clinical strains. This activity appears related to EOs composition. Particularly cv 'Abrialis' and 'R.C.' showing the highest antimicrobial activity, were rich in the specific constituents: linalool (38.17 and 61.98%), camphor (8.97 and 10.30%), 1, 8-cineole (6.89 and 8.11%, respectively). These EOs could find potential applications in food biopreservation and in surface decontamination, even in hospitals, and deserve deeper investigations. Abstract :